Isolation of Biomolecules from the Leaves of Lecaniodiscus cupanoides Sapindaceae ), a Plant used in Traditional Medicine in Benin - TOKOUDAGBA, Kossi Jean-Marie Denis; HOUNGBEME, GOUTON ALBAN (My University, 2023)
The aim of the present study was to identify the structure of the bioactive molecules in the active ethyl acetate fraction of the hydroethanolic extract of Lecaniodiscus cupanoides (Sapindaceae), a Beninese plant used in the treatment of microbial infections. We prepared the extract from powdered dried leaves. We fractionated the hydroethanol extract using the liquid-liquid extraction method with solvents of increasing polarity. The active ethyl acetate fraction obtained after bioguided fractionation of the hydroethanol extract on bacterial strains was purified by a series of atmospheric pressure column chromatographic methods coupled with thin layer chromatography. At the end of this purification process, three compounds, including a flavonoid and two fatty acids, were isolated and identified by interpretation of 1H NMR, 13C NMR and mass spectrometry spectra. These were: 2-(3,4-dihydroxyphenyl)-3,5,7-trihydroxy-2,3-dihydrochromen-4-one;(E)-3-(3,4-dihydroxyphenyl)-2-(3-(3,4-dihydroxyphenyl) acryloyloxy) propanoic acid and (E)octadec -9- enoic acid (oleic acid). The added value of this work lies in the fact that these three molecules have never before been identified in this plant, and therefore represent a potential avenue for the development of a therapeutic arsenal to combat microbial infections.
Keywords: Lecanioides cupanoides (Sapindaceae) isolation; chromatographic methods; spectrometric analysis.